Population structure and group size of geladas (Theropithecus gelada) at Chenek, Simien Mountains National Park, Ethiopia. (28th April 2017) - Ejigu, Dessalegn; Bekele, Afework
Abstract: The aim of this study was to investigate population structure and group size of geladas ( Theropithecus gelada ) at Chenek, Simien Mountains National Park. The study was carried out from January 2010 to June 2011 using total count method by classifying the study site into five different blocks. Size of the group was determined by counting individuals of geladas within an hour interval. A total of 397 geladas were counted and the ratio of adult males to adult females was 1 : 1.25, and this difference showed statistical significant ( t  = 8.157, P  < 0.05). There was also significant difference between adult females with juveniles and infants ( t  = 21.027, P  < 0.05). Population structure of geladas in a band comprised a single reproductive male and a number of females, subadults, juveniles and infants. Fission and fusion of individual geladas among different bands were observed during the study period. Geladas at the study site showed population growth and were seen competing for available food. They also stole food from local people and tourists and were seen to be interactive with people. Thus, the interference of people and livestock within the geladas natural habitat should be minimized to avoid human disturbance on the species and its natural habitat.